2013
DOI: 10.2147/ijn.s45031
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and in vivo pharmacokinetics of nanostructured lipid carriers loaded with oleanolic acid and gentiopicrin

Abstract: Background:The purpose of this work was to develop nanostructured lipid carriers (NLCs) loaded simultaneously with oleanolic acid and gentiopicrin. Methods: An aqueous dispersion of NLCs was prepared successfully using a film-ultrasonic method, with glycerin monostearate as the solid lipid and oleic acid as the liquid lipid. Poloxamer 188 was used as the surfactant. A central composite design was used to optimize the technologic parameters. The characteristics of the NLCs were then investigated. Results: The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 26 publications
4
41
0
Order By: Relevance
“…The dose selection was based on previous reports from the literature. 16,28,29 Our results showed that OA-MVLs were more effective for inhibiting tumor growth ( Figure 9A) and prolonging survival times ( Figure 9B) in a dose-dependent manner, compared to the saline and OA solution. The enhanced antitumor activity of OA-MVLs may be due to the slow-release effect which was confirmed by both release profile in vitro and plasma pharmacokinetic studies in vivo.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…The dose selection was based on previous reports from the literature. 16,28,29 Our results showed that OA-MVLs were more effective for inhibiting tumor growth ( Figure 9A) and prolonging survival times ( Figure 9B) in a dose-dependent manner, compared to the saline and OA solution. The enhanced antitumor activity of OA-MVLs may be due to the slow-release effect which was confirmed by both release profile in vitro and plasma pharmacokinetic studies in vivo.…”
Section: Discussionmentioning
confidence: 81%
“…Drug administration and blood sample collection Two groups of five rats each were treated with OA solution or OA-MVLs at a single dose of 10 mg/kg via subcutaneous (sc) injection; 16 the OA solution was prepared by dissolving OA in polyethylene glycol 400 (0.2%) and further diluting with saline for injection. Blood samples were collected from the ophthalmic veins after administration.…”
Section: Pharmacokinetic Evaluation Of Oa-mvls In Ratsmentioning
confidence: 99%
See 3 more Smart Citations